A Familial Case of Multiple Endocrine Neoplasia 2A: From Morphology to Genetic Alterations Penetration in Three Generations of a Family - Lan Chen; Jing-Xin Zhang; Dong-Ge Liu; Hong-Gang Liu (Diagnostics, 2023)
This paper illustrates a rare syndrome of multiple endocrine neoplasia type 2A (MEN2A) in a family of three generations. In our case, the father, son and one daughter developed phaeochromocytoma (PHEO) and medullary thyroid carcinoma (MTC) over a period of 35 years. Because of the metachronous onset of the disease and lack of digital medical records in the past, the syndrome was not found until a recent fine needle aspiration of an MTC-metastasized lymph node from the son. All resected tumors from the family members were then reviewed and supplemented with immunohistochemical studies, previously wrong diagnoses were then corrected. Further molecular study of targeted sequencing also revealed a RET germline mutation (C634G) in the family tree including the three members with onset of the disease and one granddaughter who had no disease at the time of testing. Despite the syndrome being well-known, it may still be misdiagnosed because of its rarity and long disease onset. A few lessons can be learned from this unique case. Successful diagnosis requires high suspicion and surveillance and a tri-level methodology including a careful review of family history, pathology and genetic counselling.